2015
DOI: 10.1186/s13287-015-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Rho kinase inhibitor Y-27632 promotes the differentiation of human bone marrow mesenchymal stem cells into keratinocyte-like cells in xeno-free conditioned medium

Abstract: IntroductionBone marrow mesenchymal stem cells (BMSCs), which have the ability to self-renew and to differentiate into multiple cell types, have recently become a novel strategy for cell-based therapies. The differentiation of BMSCs into keratinocytes may be beneficial for patients with burns, disease, or trauma. However, the currently available cells are exposed to animal materials during their cultivation and induction. These xeno-contaminations severely limit their clinical outcomes. Previous studies have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 42 publications
(62 reference statements)
0
27
2
2
Order By: Relevance
“…Furthermore, supplementary Y‐27632 can regulate the ability of stem cells to self‐renew and differentiate into derivatives of all three germ layers . More importantly, Y‐27632 was shown to greatly increase the long‐term proliferation of primary human keratinocytes, and unexpectedly, to enable these cells to efficiently bypass senescence and become immortal without a detectable cell crisis . Moreover, Y‐27632 could prevent mesenchymal stem cell (MSC) sheets from detaching and maintain the multilayered proliferation of confluent MSCs .…”
Section: Discussioncontrasting
confidence: 94%
“…Furthermore, supplementary Y‐27632 can regulate the ability of stem cells to self‐renew and differentiate into derivatives of all three germ layers . More importantly, Y‐27632 was shown to greatly increase the long‐term proliferation of primary human keratinocytes, and unexpectedly, to enable these cells to efficiently bypass senescence and become immortal without a detectable cell crisis . Moreover, Y‐27632 could prevent mesenchymal stem cell (MSC) sheets from detaching and maintain the multilayered proliferation of confluent MSCs .…”
Section: Discussioncontrasting
confidence: 94%
“…The earlier studies have reported that Y-27632 can decrease cytoskeletal tension and contractility and can inhibit osteogenesis of MSC and osteoblasts (McBeath et al 2004;Khatiwala et al 2009;Kilian et al 2010;Shih et al 2011). In contrast, Y-27632 shows differentiation lineage specificity; Y-27632 can induce stem cells to differentiate into adipocytes, neuron cells, endothelial cells, and keratinocytes (McBeath et al 2004;Pacary et al 2006;Joo et al 2012;Li et al 2015). Although Y-27632 has been used as a multifunctional agent, the underlying molecular mechanism that determines inhibition or induction of stem cell differentiation remains unclear.…”
Section: Differentiationmentioning
confidence: 99%
“…In order to enhance the differentiation of MSCs to respiratory epithelium we investigated the impact of ROCK inhibition. ROCK inhibition using Rho kinase inhibitors like Y‐27632 has been shown to promote the induction efficiency, self‐renewal, and differentiation of MSCs towards the keratinocyte like cells with good expression of cytokeratin 14 and cytokeratin 5 in the presence keratinocyte‐conditioned medium (Li et al, ). Thus, it was envisaged that this approach can also further push the epithelial differentiation of MSCs in the presence of biocomposite films.…”
Section: Resultsmentioning
confidence: 99%